Analysis of Learning Obstacles in the Damair Rules Material in Arabic Language Learning - Lislis Cahyati; Maman Abdurahman; Nalahuddin Saleh (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze learning obstacles in mastering the rules of damair, particularly damair munfa?ilah and damair mutta?ilah, in Arabic language learning among Grade X.1 students at Madrasah Aliyah Al Inayah, Bandung. The research employs a qualitative approach using a case study design. Data were collected through diagnostic tests and interviews, involving students who had previously studied the topic of damair. Interview participants were selected using maximum variation sampling, a type of purposive sampling that considers the diversity in students' performance levels. The analysis revealed that students' learning obstacles can be classified into three categories based on Brousseau’s theory: (1) ontogenic obstacles, related to students’ limited vocabulary and cognitive readiness; (2) epistemological obstacles, involving misconceptions and conceptual errors in understanding the rules of damair; and (3) didactical obstacles, resulting from unsystematic instructional approaches, particularly in explaining the function of damair within i‘rab structures, which hinder students’ comprehensive understanding of grammatical relations. The findings of this study are expected to serve as a basis for developing more targeted teaching strategies, thereby improving students’ understanding of damair rules and supporting the overall enhancement of their Arabic language proficiency.